Clinical significance of pathologically detected lesions in reduction mammoplasty - Arslan, Remzi (Journal of Surgery and Medicine, 2022)
Background/Aim: Breast reduction surgery is performed for various reasons, especially macromastia. Although the mammoplasty material obtained after surgery is generally accepted as normal breast tissue, incidental breast cancer or precursor lesions of breast cancer are also observed in these materials. Detection of these lesions will provide important information both for the risk developing breast cancer in the normal population and for the early treatment of these lesions. Our study aimed to investigate the rate of occurrence of high-risk lesions, such as atypical ductal hyperplasia (ADH), atypical lobular hyperplasia (ALH), and carcinoma in situ (DCIS, LCIS) and the relationship of these lesions with patient age and weight of the resected material. Methods: This study was a retrospective cohort study examining incidentally detected pathological lesions after examining reduction mammoplasty materials after breast reduction in our pathology department between 2011 and 2021. None of the cases had been previously diagnosed with breast cancer. The cases were pathologically classified as benign lesions, high-risk lesions with atypia, and in situ carcinoma. The association of atypical high-risk lesions with age (> 40 and ≤ 40 years) and resection weight was evaluated. Results: The surgical materials of 288 breasts were evaluated in a total of 144 women. The mean age of the patients was 38.9 years. Atypical high-risk lesions, such as ADH, ALH, and DCIS were detected in seven patients (4.8%). İnvasive cancer was not observed. The mean age of the patients with risky lesions was 45.98 years, and the mean weight of these lesions was 2,045 grams. Cases with high-risk lesions were older (P = 0.041) and had a higher resection weight (P = 0.003). Conclusion: The findings in our study reveal the necessity for mandatory histopathological examination of reduction mammoplasty materials. This examination is even more important in terms of high-risk lesion detection, especially in patients over 40 years and those with a high resection weight. In these cases, taking more tissue samples than used for the other situation for examination is recommended.